INDICATORS OF SOCIAL NETWORK ADDICTION IN COLLEGE STUDENTS FROM LIMA - Araujo Robles, Elizabeth Dany (2016)
The study was conducted on 200 students from a private university in Lima (150 female), who belong to four academic programs: Psychology, Administration and International Business, Pharmacy and Biochemistry, and Obstetrics. The objective of the study is to assess the intensity of three social network addiction dimensions: obsession for social networking, lack of personal control about using social networks, and excessive use of social networks. The Social Networking Addiction Questionnaire from Escurra and Salas (2014) was used. Results show low levels for all indicators assessed. Males' scores were significantly higher than females' only in the obsession for social networking indicators. In addition, for all three dimensions, the Administration program students obtained the highest scores, and the Psychology and Obstetrics program students obtained the lowest. The implications of the results found are discussed.